Implementasi Pasal XX (b) dan (g) General Agreement on Tariffs and Trade dalam Penyelesaian Sengketa di World Trade Organisation - Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2012)
There is a mutual relation between international trade and environment. International trade may give negative effects to the environment. The problems that will be studied are, first, how is the implementation of Article XX (b) and (g) of GATT in the dispute settlement at WTO? Second, why is there differences in interpretation method toward Article XX (b) and (g) of GATT by Panel and Appellate Body in dispute settlement at WTO? This research os a normative research and is analyzed qualitatively. The result of the research concludes that: first, panel and Appellate Body have differences in implementing Article XX (b) and (g) of GATT. This is caused by the different interpretation done by Panel and Appellate Body; second, the difference in the interpretation of Article XX (b) and (g) of GATT by Panel and Appellate Body in the settlement of those three cases is resulted from the lack of understanding of the Panel on the interpretation way as stipulated in Article 2(3) of DSU and lack of partisanship from the Panel to the importance of health, plants, animals, and environment protections.International trade, panel, appellate body, negative effects